York dictionary of personal computing and the internet - Collin, S.M.H (New york york press, 1998)
The vocabulary of personal computing and the Internet continues to explode as new hardware and software becomes available. This revised and updated edition with 2,000 terms defined and explained now grows far beyond the standard personal commuting terms to include new words and acronyms generated by Windows 95 and 98, E-mail, FTP, Telnet, IRC, the Web, Finger, Java, Active X, scripting, plug-in technology, and much more. The dictionary is arranged in a glossary format, with a paragraph defining each term, and includes user tips on how to get the best performance from the system, software, or Int
Keywords: Computer -- dictionaries; Internet -- dictionaries